Analisis Ketersediaan Air Pdam Kota Bengkalis - Abdul Rasyid; Siswanto Siswanto; Trimaijon Trimaijon (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Water sources used by the Regional Water Company (RWC) is derived from the Wonosari’s reservoir of Bengkalis City which covers about 6 acres, but the volume of the reservoir storage is not sufficient to supply water in the city of Bengkalis. Therefore it is necessary to estimate wether the water from the canals of PT. Meskom Agrosarimas can fulfill the water needs for customers PDAM Bengkalis. there are three methods used to analyze the number of people, namely the geometric method, arimatik method, and the method of least squares. Reservoir water volume calculation was analyzed using the FJ Mock method, while the volume of water of canal PT. Meskom was analyzed using Rational Method. Calculation of population growth of Bengkalis District using Arithmetic method for the population of 10 years to come, namely in 2025 amounted to 112 667 inhabitants. Clean water needs Bengkalis District’s residents in 2015 amounted to 143 liters / sec and for 2025 is 180 liters / sec. Water volume of the reservoir that can be utilized to meet the needs of raw water amounted to 109 005 m3.Keywords: Water Availability, Regional Water Company (RWC)